A multicriteria decision model for selecting a portfolio of oil and gas exploration projects - Lopes,Yuri Gama (2013)
As well as exploratory activity being at the heart of and guiding the future of the oil industry, it is fundamental that there be a comprehensive analysis covering the various factors and nuances that arise in the selection of exploration projects. Moreover, it is essential that a decision model enables the decisionmaker's preferences to be addressed in a structured (and methodologically correct) way, and one which is easy to understand and to apply in a real-world. Therefore, this paper proposes a multicriteria decision model which underpins using a deterministic procedure for selecting a portfolio of oil and gas exploration projects and thereafter a reality-based application is set out, based on a decision making context within Petrobras.